Hydrogels for localized chemotherapy of liver cancer: a possible strategy for improved and safe liver cancer treatment - Jianyong Ma; Bingzhu Wang; Haibin Shao; Songou Zhang; Xiaozhen Chen; Feize Li; Wenqing Liang (Taylor & Francis Group, 2022)
The systemic drug has historically been preferred for the treatment of the majority of pathological conditions, particularly liver cancer. Indeed, this mode of treatment is associated with adverse reactions, toxicity, off-target accumulation, and rapid hepatic and renal clearance. Numerous efforts have been made to design systemic therapeutic carriers to improve retention while decreasing side effects and clearance. Following systemic medication, local administration of therapeutic agents allows for higher 'effective' doses with fewer side effects, kidney accumulation, and clearance. Hydrogels are highly biocompatible and can be used for both imaging and therapy. Hydrogel-based drug delivery approach has fewer side effects than traditional chemotherapy and can deliver drugs to tumors for a longer time. The chemical and physical flexibility of hydrogels can be used to achieve disease-induced in situ accumulation as well as subsequent drug release and hydrogel-programmed degradation. Moreover, they can act as a biocompatible depot for localized chemotherapy when stimuli-responsive carriers are administrated. Herein, we summarize the design strategies of various hydrogels used for localized chemotherapy of liver cancer and their delivery routes, as well as recent research on smart hydrogels.